2020
DOI: 10.1101/2020.07.21.213421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycorrhizal symbiosis alleviates plant water deficit within and across plant generations via plasticity

Abstract: SummaryPhenotypic plasticity is essential for organisms to adapt to local ecological conditions. Little is known about how mutualistic interactions, such as arbuscular mycorrhizal (AM) symbiosis, mediate plant phenotypic plasticity and to what extent this plasticity may be heritable (i.e. transgenerational effects).We tested for plant plasticity within- and across-generations in response to AM symbiosis and varying water availability in a full factorial experiment over two generations, using the perennial apom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…This suggests that embryo modifications were not the only mechanism driving our observed transgenerational effects and points to other mechanisms, such as heritable epigenetic modifications or hormonal balance in embryos (Herman & Sultan, 2011; Rottstock et al ., 2017). Also, even though any parental effects are likely to fade away with time (Dechaine et al ., 2015; Puy et al ., 2020b), the effects associated with differences in seed mass seem to fade away faster (Latzel et al ., 2010). Meanwhile, the effect of seed mass on growth rate lasted until the 24 th day (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that embryo modifications were not the only mechanism driving our observed transgenerational effects and points to other mechanisms, such as heritable epigenetic modifications or hormonal balance in embryos (Herman & Sultan, 2011; Rottstock et al ., 2017). Also, even though any parental effects are likely to fade away with time (Dechaine et al ., 2015; Puy et al ., 2020b), the effects associated with differences in seed mass seem to fade away faster (Latzel et al ., 2010). Meanwhile, the effect of seed mass on growth rate lasted until the 24 th day (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The later, transgenerational phenotypic plasticity – in short, transgenerational plasticity – occurs when the phenotype of progeny is influenced by the environmental conditions experienced by the parents (also referred to as parental or transgenerational effects; Herman et al ., 2014; Turcotte & Levine, 2016). The great majority of existing studies on transgenerational plasticity focus on phenotypic responses to abiotic factors (Galloway & Etterson, 2007; Auge et al ., 2017; Bej & Basak, 2017; Puy et al ., 2020a) and have generally overlooked the role of biotic interactions (Alonso et al ., 2019; Puy et al ., 2020b), such as competition between organisms. However, these biotic interactions are considered leading factors for controlling species coexistence, biodiversity maintenance, and ecosystem functioning (Van der Putten et al ., 2013; Kraft et al ., 2015; Valladares et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct effects include increasing seed size or nutrients stored in endosperm, and indirect effects include that changing the trait plasticity of parental plant, which may lead to transgenerational transmission of phenotypic plasticity in functional adaptation (Herman and Sultan, 2011;Varga et al, 2013;Varga and Kytöviita, 2014;Yin et al, 2019). It is noteworthy that the transgenerational effect can operate via two mutually non-exclusive mechanisms, seed provisioning (seed size, seed nutritional quality, or hormonal balance), and environmentally induced heritable epigenetic modifications in offspring (Puy et al, 2022). Here, we review the effects of AM symbiosis on female functional fitness of host plants from two aspects: the effects of AM symbiosis on seed germination and the growth performance of germinated seedlings.…”
Section: E Ects On Seed Germination and Seedlings Performancementioning
confidence: 99%
“…The greater legume content, and lower readily available soil P status, on organic dairy farms was also associated with greater forage legume root colonization by mycorrhizae (AMF) and a shift in AMF community composition, along with greater legume biological N 2 fixation (Schneider et al, 2015(Schneider et al, , 2017a. A fascinating recent study (Puy et al, 2021) has shown that plant phenotypic changes incurred by water availability and by parent plant AMF association, is transferred to the next generation of plants, thus conferring environmental stress resiliency across plant generations. One can speculate thus that enhanced crop resiliency to climate stresses often observed on organic farms is due to some degree to greater AMF and other beneficial plant-soil microbe interactions.…”
Section: Biodiversity and Soil Biotamentioning
confidence: 99%